KAPASITAS HUKUM INDONESIA SEBAGAI ANGGOTA TIDAK TETAP DEWAN KEAMANAN PBB DALAM PENANGANAN MASALAH PERUBAHAN IKLIM GLOBAL - Natalia Yeti Puspita (Universitas Pendidikan Ganesha, 2020)
Climate change is a serious problem that threatens humanity in the world, and this can be categorized as a non-traditional security problem known as human security. Climate change in the world is marked by the increase in the temperature of the earth's air and rising sea levels due to the melting of ice in the polar regions. This condition will cause disasters both natural disasters such as drought and forest fires, as well as non-natural disasters such as conflicts and epidemics, which will ultimately threaten world peace and security. In January 2019, Indonesia was officially elected as a non-permanent member of the UN Security Council. The election of Indonesia is evidence of the confidence of the international community in Indonesia's diplomatic capabilities. Indonesia will carry out its role as a non-permanent member of the UN Security Council for two years, from 1 January 2019 to 31 December 2020. With its position as a non-permanent member of the UN Security Council, Indonesia is expected to be actively involved in efforts to tackle climate change. Based on this, in this paper, the author will raise the topic of